Poisoning by Astragalus garbancillo var. garbancillo in sheep in Northwestern Argentina - Micheloud, Juan Francisco; Marin, Raul Eduardo; Martinez, Agustin; Martinez, Olga Gladys; Gimeno, Eduardo Juan; Gardner, Dale R. (2018)
Several toxic plants produce lysosomal storage of glycoproteins and mainly nervous clinical disorders. A disease caused by the consumption of Astragalus garbancillo var. garbancilloin sheep from northwestern Argentina is described here. The affected animals presented weight loss, listlessness, staggering gait and ataxia. Histopathological studies revealed cellular vacuolation in several organs, mainly in the CNS. The material accumulated in the cells was positive for lectins LCA (Lens culinaris agglutinin), sWGA (succinyl–Triticum vulgaris agglutinin) and Con A (Concanavalin A).Finally, the presence of toxic levels of swainsonine was detected in composite samples of the plant. Poisoning by Astragalus garbancillo var. garbancillo was characterized as α-mannosidosis of plant origin.